2012
DOI: 10.1104/pp.111.181875
|View full text |Cite
|
Sign up to set email alerts
|

Drought and Salt Stress Tolerance of an Arabidopsis Glutathione S-Transferase U17 Knockout Mutant Are Attributed to the Combined Effect of Glutathione and Abscisic Acid      

Abstract: Although glutathione S-transferases (GSTs) are thought to play major roles in oxidative stress metabolism, little is known about the regulatory functions of GSTs. We have reported that Arabidopsis (Arabidopsis thaliana) GLUTATHIONE S-TRANSFERASE U17 (AtGSTU17; At1g10370) participates in light signaling and might modulate various aspects of development by affecting glutathione (GSH) pools via a coordinated regulation with phytochrome A. Here, we provide further evidence to support a negative role of AtGSTU17 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
217
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(226 citation statements)
references
References 53 publications
6
217
1
2
Order By: Relevance
“…The present study showed that C. vulgaris treated with NaCl at concentrations 10 -7 -10 -4 M was characterized by a smaller number of algae cells compared to the controls. This finding is consistent with data in literature according to which the salinity inhibits mitotic divisions, causes a slowdown in the elongation growth of cells, and, ultimately, reduces the rate of growth of leaves and roots (Munns and Tester 2008;Chen et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…The present study showed that C. vulgaris treated with NaCl at concentrations 10 -7 -10 -4 M was characterized by a smaller number of algae cells compared to the controls. This finding is consistent with data in literature according to which the salinity inhibits mitotic divisions, causes a slowdown in the elongation growth of cells, and, ultimately, reduces the rate of growth of leaves and roots (Munns and Tester 2008;Chen et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, Physiol Mol Biol Plants (April-June 2017) 23(2):249-268 253 supplementation of wild type plants with exogenous GSH resulted in higher ABA content and a similar phenotype to that seen in the mutant, as well as greater drought tolerance. Glutathione application induced higher levels of ABA, the plant hormone that controls seed germination, regulates stomatal aperture, and reduces transpiration rate (Chen et al 2012). Drought stress resulted in leaf rolling in Ctenanthe setosa (Rosc.)…”
Section: Droughtmentioning
confidence: 99%
“…GST expression in plants is induced by phytohormones such as SA, ethylene, cytokinin, auxin, ABA (Marrs 1996), methyl jasmonate (Moons 2003), and brassinosteroids (Deng et al 2007). Chen et al (2012) demonstrated that GST overexpressed in Arabidopsis thaliana plants had a signaling role and it regulated plant development by maintaining GSH pools. The mutant plant atgstu17 synthesized higher levels of GSH and ABA when compared to the wild type.…”
Section: Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule has many other functions in plant cells including even the induction of the transcription of gst genes [19] Under environmental stress conditions, plants raise the concentration of GSH in especially foliar tissues as a part of their acclimation strategy via antioxidative defense systems [30]. However, Chen et al [31] concluded that the higher ratio of reduced to oxidized GSH or, glutathione / glutathione disulfide (GSH/GSSG), the rate of GSH biosynthesis and the capacity of its redox cycling, rather than GSH accumulation, might be essential for drought resistance in plants; so, one could/couldn't measure elevated glutathione levels, or even decreased levels might be detected. This means that, even if there observed little change in GSH amount during summer period, the GSH/GSSG redox state might be changed towards being more oxidized, more reduced, or not at all.…”
Section: Total Glutathione S-transferase Activity Changes In Cytosolimentioning
confidence: 99%